Melodrama, victimhood, and complicity in Whitney Terrell’s The Good Lieutenant - M Ikbal M Alosman,; Ruzy Suliza Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article examines how melodramatic political discourse shapes portrayals of victimhood, heroism, and culpability in Whitney Terrell’s The Good Lieutenant. Building on Elisabeth Anker’s account of melodrama—which frames the nation as a virtuous victim whose pain licenses redemptive force—we show how the novel both draws on and strains this moral grammar. Methodologically, we translate Anker’s ideas into a practical toolkit for literary analysis, focusing on temporal design, role grammar, the rhetoric of victimhood, and the affective economy through which private loss becomes public meaning. Two axes organise the readings: first, the centering of American soldiers’ suffering as the main source of pathos; second, the conditional and often short-lived recognition of Iraqi civilian pain. While reverse chronology, scenes of desecration, and gendered vulnerability lend American figures moral centrality, the book also unsettles melodramatic binaries by foregrounding complicity, failed rescue, and the limits of redemption. We conclude that The Good Lieutenant exemplifies the ambivalence of recent war fiction: it critiques the Iraq War’s legitimating stories even as it remains entangled in the forms that elevate some victims over others.